EMISSIONS AND FUEL CONSUMPTION OF SINGLE CYLINDER DIESEL ENGINE USING PLASTIC FUEL - Sudrajad, Agung; Wiyono, Slamet; Jannah, Miftahul; Abdullah, Syarif; Listijorini, Erny (Trends in Mechanical Engineering Research, 2023)
This paper deals with the exhaust emission of plastic fuel on single cylinder diesel engine. The objectives of this research are to analyze the fuel consumption and the emission characteristic of a single cylinder diesel engine that are using plastic fuel compared to usage of ordinary diesel that are available in the market. This paper describes the setups and the procedures for the experiment which is to analyze the emissions characteristics and fuel consumption of diesel engine due to usage of the both fuels. The experiment used diesel engine with no load which means no load exerted on it. Detail studies about the experimental setup and components have been done before the experiment started. The obtained data indicated that the diesel fuel is better than waste plastic disposal fuel in term of fuel consumption, emissions of carbon monoxide (CO) and emissions of carbon dioxide (CO2). The successful of the project have been stated which is engine is able to run with plastic fuel but the engine needs to run by using diesel fuel first, then followed by plastic fuel and finished with diesel fuel as the last fuel usage before the engine turned off.